Late-orogenic Variscan magmatism: The case of quartz monzodiorite dykes from the Blanice Graben, southern Bohemia - Vrana,S.; Janousek,V. (Journal of the Czech Geological Society, 2006)
Pyroxene-biotite quartz monzodiorite of the Stepanovice dyke (3 km long and up to 50 m wide), together with additional small occurrences further north, is associated with the Late Variscan Blanice Graben in the Moldanubian Zone of southern Bohemia. The texture is subophitic, fine- to medium-grained, with skeletal crystals of ilmenite and zircon. This, together with rare amygdaloidal texture, indicates a rapid cooling of the melt emplaced at shallow (subvolcanic) crustal levels. Quartz monzodiorites are metaluminous (A/CNK = 0.79-0.86), high-K calc-alkaline rocks straddling the boundary to the shoshonitic domain. A characteristic feature in the Primitive-Mantle normalized spider plots are LREE/HREE enrichments as well as Nb-Ti-P troughs, resembling magmas derived in continental arc settings. The Nd isotopic compositions of two samples (ε290Nd &#150 -2.6 and -3.1) correspond to single-stage Nd depleted-mantle model ages of 0.97 and 1.02 Ga; the strontium is unradiogenic (87Sr/86Sr290 = 0.7064 and 0.7066). The studied quartz monzonite dykes show a geological position, petrologic and whole-rock geochemical affinity to pyroxene microgranodiorite-quartz monzodiorite of the adjacent, &#126 270 Ma old Sevetin dyke swarm and the quartz micromonzodioritic Susice dyke swarm further 75 km to the WNW. All these late Variscan (?Permian) basic-intermediate magmas seem to have intruded in extensional regime, following the orogenic collapse. The attendant crustal thinning could have led to upwelling and adiabatic decompression melting of the local, by Late Palaeozoic subduction-modified, lithospheric mantle. The Sr-Nd isotopic data point to assimilation of crustal material by rather primitive, slightly enriched mantle-derived magmas.
Keywords: Quartz monzodiorite; petrology; geochemistry; petrogenesis; Bohemian Massif; Variscan orogeny